METODE PEMBELAJARAN BERKIRIM SALAM DAN SOAL TERHADAP HASIL BELAJAR SISWA PADA TEMA INDAHNYA NEGERIKU KELAS IV SDN 6 SUWAWAL - Fine Reffiane; Dian Ratna Sari (Universitas PGRI Semarang, 2014)
This research is based on the fact that students are still confused in accepting materials given by teachers in the learning proces inside the classroom. This condition makes the students result be low, teacher explains or speaks much in the classroom so they are less entusiastic in learning the materials so they cannot accept well what the teacher give to them. The problem of this research is that is there any effect on learning sending greeting and exercises toward the students study result on the theme what a beautiful country i have, grade IV students of SDN 6 Suwawal. The purpose to be achieved is that to find out is there any effect on learning sending and greeting and exercises toward the students study result on the theme what a beautiful country i have grade IV students of SDN 6 Suwawal?é?á?é?á?é?á .This is a kuantitative research. The population of this research are all students of grade IV in SDN 6 Suwawal Jepara. The sampling taken are 40 students using probability sampling technique especially cluster sampling. Data of this research is gained from the observation on students activity to get score on phsicomotoric aspect including the test to know the students study result on cognitive aspect. The research design used is pretest posttest control group design.Based on the result analysis on the data research by using t?óÔé¼ÔÇ£ test separated, is gained 2,447 tcount of cognitive score, 2,243 tcount of tcount phsicomotoric with ttabel for both is 2, 021 on 5% significancy level. So, tcount > ttabel and Ho is denied. Average increase on cognitive study result on students grade IV of SDN 6 Suwawal Jepara before given the treatment is 50% and after the treatment is 100%. The average psicomotoric study result is 80%. So, it can be concluded that there is effects on learning sending and greeting and exercises toward the students study result on the theme what a beautiful country i have grade IV students of SDN 6 Suwawal. The recomendation that the researcher can give is that the use of sending greeting and exercises method should be applied on small class only or class with not more than 25 students in it because it is needed relatively a lot of time in the application of this kind of research method.